Quantifying Neodiprion sertifer nucleopolyhedrovirus DNA from insects, foliage and forest litter using the quantitative real‐time polymerase chain reaction. (26th December 2012) - Krokene, Paal; Heldal, Inger; Fossdal, Carl G.
This qPCR assay can be used to determine important aspects of the biology of NeseNPV (e.g. virus levels in different insect life stages and in their microhabitats on pine foliage and in forest litter).